1999
DOI: 10.1021/jp990985a
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study for Selective Oxidation of Methane with NOx(x= 1, 2)

Abstract: A reaction model for the conversion of methane to C1-oxygenates (methanol and formaldehyde) with NO x (x = 1, 2) has been proposed theoretically using the ab initio molecular orbital method. The geometric and electronic structures for all the present molecules have been calculated by means of the MP2 (frozen core)/6-311++G(2d,p) level of theory. On the basis of the optimized structures, the single point calculations of the energies are carried out at the CCSD(T) level with the same basis sets. Through the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 30 publications
(32 reference statements)
5
53
0
Order By: Relevance
“…Yamaguchi and co-workers [14,15] conducted a theoretical study of the selective oxidation of CH 4 by NO x at 800 K and 1 bar, with particular emphasis on NO x -induced Habstraction from CH 4 based on ab initio molecular orbital theory. These calculations confirmed that NO 2 + CH 4 has two important product channels forming CH 3 and either of the two isomers HONO (R11) and HNO 2 (R12), where the latter is favored by a slightly lower energy barrier.…”
Section: No X /Alkane Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yamaguchi and co-workers [14,15] conducted a theoretical study of the selective oxidation of CH 4 by NO x at 800 K and 1 bar, with particular emphasis on NO x -induced Habstraction from CH 4 based on ab initio molecular orbital theory. These calculations confirmed that NO 2 + CH 4 has two important product channels forming CH 3 and either of the two isomers HONO (R11) and HNO 2 (R12), where the latter is favored by a slightly lower energy barrier.…”
Section: No X /Alkane Reactionsmentioning
confidence: 99%
“…A comparison with the corresponding initiation reaction CH 4 + O 2 CH 3 + HO 2 indicates that the energy barrier is lowered by about 20-25 kcal/mol when NO 2 is the reactant rather than O 2 , making NO 2 + CH 4 an important initiation reaction in the CH 4 /O 2 /NO x system. The reaction NO + CH 4 HNO + CH 3 (−R28) has a barrier height of magnitude similar to that of CH 4 + O 2 [14] and is not important for initiation. Chan et al [46] presented ab initio calculations of the NO 2 -induced initiation of different aliphatic hydrocarbon fuels at 600-1100 K, including CH 4 and C 2 H 6 , based on a level of theory similar to that of Yamaguchi and co-workers.…”
Section: No X /Alkane Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…***Yield: Total conversion · Selectivity. significantly lower barrier for H-atom abstraction from alkanes by NO 2 [20,21]. Scheme 1 outlines the mechanism of the NO x -mediated oxidation of alkanes by dioxygen.…”
Section: (Outlet)]mentioning
confidence: 99%